Topological optimization of internal patterns and support in additive manufacturing - Gardan, Nicolas; Schneider, Alexandre (Journal of manufacturing systems, 2015)
•Optimization of additive manufacturing product with numerical simulation.•Topological optimization dedicated to additive manufacturing.•Knowledge based management of additive manufacturing for numerical integration.•Weight saving by coupling topological optimization and additive manufacturing. Rapid prototyping (RP) and more generally Additive Manufacturing (AM) enable the manufacture of complex geometries, which are very difficult to build with classical production. There are numerous technologies that are using different kind of material. For each of these, there are at least two materials: the production material and the support one. Support material is, in most cases, cleaned and becomes a manufacturing residue. Improve the material volume and the global mass of the product is an essential aim surrounding the integration of simulation in additive manufacturing process. Moreover the layer-by-layer technology of additive manufacturing allows the design of innovative objects and the use of topological optimization in this context can create a very interesting combination. The purpose of our paper is to present a methodology and a tool, which allow the use of topological optimization for the preparation of model for RP and AM.